LOCAL WISDOM AS A MEANS TO FOSTER INDEPENDENCE IN MATHEMATICS LEARNING - Darmawan Harefa (Universitas Nias Raya, 2025)
Mathematics learning is often perceived by students as difficult and abstract, leading to dependence on teacher guidance and hindering the development of independent learning. This study examines the role of local wisdom as a means to build independence in mathematics learning, specifically at SMA Negeri 1 Teluk Dalam, South Nias. Through a literature review, it was found that integrating local values and culture into the mathematics learning process not only enhances conceptual understanding contextually but also motivates students to learn independently. Local wisdom, such as geometric patterns in traditional weaving, indigenous life philosophies, and traditional building structures, can serve as relevant and engaging learning media for students. This approach helps students develop critical and creative thinking skills while boosting their confidence in solving mathematical problems. Furthermore, learning based on local wisdom strengthens students’ cultural identity and fosters pride in their local heritage. This study recommends the development of learning modules that integrate local wisdom and teacher training as efforts to optimally support students’ independent learning. The implications of this review suggest that local wisdom can be an effective strategy to improve the quality of mathematics education and the development of students’ independent character within the school environment.